Zariski multiplicity conjecture in families of non-degenerate singularities - Brzostowski, Szymon; Krasiński, Tadeusz; Oleksik, Grzegorz (Analitic and Algebraic Geometry 4, 2022)
We give a new, elementary proof of the Zariski multiplicity conjecture in μ-constant families of non-degenerate singularities.